2014
DOI: 10.1016/j.cortex.2013.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Modulating effect of COMT genotype on the brain regions underlying proactive control process during inhibition

Abstract: Jaspar M., Genon S., Muto V., Meyer C., Manard M., Dideberg V., Bours V., Salmon E., Maquet P., Collette F. (2013). Modulating effect of COMT genotype on the brain regions underlying proactive control process during inhibition. Cortex (in press). DOI: http://dx.doi.org/10.1016DOI: http://dx.doi.org/10. /j.cortex.2013 Modulating effect of COMT genotype on the brain regions underlying proactive control process during inhibition

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 54 publications
(87 reference statements)
4
13
0
2
Order By: Relevance
“…Indeed, independently of any genetic considerations, the interfering component of the Sternberg probe recency task (Sternberg, 1966) was previously found to be associated with left PFC activity (mainly in the left IFG; Badre & Wagner, 2005;Burgess & Braver, 2010;D'Esposito et al, 1999;Jonides et al, 1998;Mecklinger et al, 2003;Nelson et al, 2003;Postle & Brush, 2004). Activation in a similar region was also observed in studies considering the impact of COMT genotype on updating and inhibitory functions, with Met allele carriers showing lesser recruitment of the left prefrontal cortex for the same level of performance (Bertolino et al, 2008;Caldu et al, 2007;Egan et al, 2001;Jaspar et al, 2014a;Jaspar et al, 2014b;Mattay et al, 2003). Together, these elements led us to hypothesize that VV homozygous people should recruit the bilateral PFC more extensively in response to interference during the probe recency task.…”
Section: Aim Of the Study And A Priori Hypothesesmentioning
confidence: 56%
See 4 more Smart Citations
“…Indeed, independently of any genetic considerations, the interfering component of the Sternberg probe recency task (Sternberg, 1966) was previously found to be associated with left PFC activity (mainly in the left IFG; Badre & Wagner, 2005;Burgess & Braver, 2010;D'Esposito et al, 1999;Jonides et al, 1998;Mecklinger et al, 2003;Nelson et al, 2003;Postle & Brush, 2004). Activation in a similar region was also observed in studies considering the impact of COMT genotype on updating and inhibitory functions, with Met allele carriers showing lesser recruitment of the left prefrontal cortex for the same level of performance (Bertolino et al, 2008;Caldu et al, 2007;Egan et al, 2001;Jaspar et al, 2014a;Jaspar et al, 2014b;Mattay et al, 2003). Together, these elements led us to hypothesize that VV homozygous people should recruit the bilateral PFC more extensively in response to interference during the probe recency task.…”
Section: Aim Of the Study And A Priori Hypothesesmentioning
confidence: 56%
“…In others words, only proactive control processes would be dependent of the midbrain dopaminergic system. Finally, our previous results had shown that VV homozygous individuals increased frontal activity related to interference during reactive control processes (Jaspar et al, 2014a;Jaspar et al, 2014b). However, as genotype-related discrepancies during reactive control were localized in the right inferior frontal operculum, an area not classically related to interference resolution in the Sternberg probe recency task (Burgess & Braver, 2010;D'Esposito et al, 1999;Jonides et al, 1998), we did not expect to observe group differences during this condition.…”
Section: Aim Of the Study And A Priori Hypothesesmentioning
confidence: 64%
See 3 more Smart Citations